2006
DOI: 10.5558/tfc82562-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lodgepole pine site index from climatic parameters in Alberta

Abstract: We sought to evaluate the impact of climatic variables on site productivity of lodgepole pine (Pinus contorta var. latifolia Engelm.) for the province of Alberta. Climatic data were obtained from the Alberta Climate Model, which is based on 30-year normals from the provincial weather station network. Mapping methods were based on ANUSPLIN, Hutchinson's thin-plate smoothing spline in four dimensions (latitude, longitude, elevation, climatic variable). Site indices based on stem analysis (observed dominant heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…Using traditional growth and yield models, it is difficult to predict forest growth under climate change because the site index is always assumed to be constant (Fontes et al 2010, Mäkelä et al 2012. Although process-based models are still widely used, recent models describing the relationships between the site index and environmental/climatic factors have the potential to facilitate the prediction of timber production in the context of environmental change (Monserud et al 2006, Albert & Schmidt 2009. In this study, we developed a climate-sensitive site index model using the GAM method.…”
Section: Climate-sensitive Site Index Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Using traditional growth and yield models, it is difficult to predict forest growth under climate change because the site index is always assumed to be constant (Fontes et al 2010, Mäkelä et al 2012. Although process-based models are still widely used, recent models describing the relationships between the site index and environmental/climatic factors have the potential to facilitate the prediction of timber production in the context of environmental change (Monserud et al 2006, Albert & Schmidt 2009. In this study, we developed a climate-sensitive site index model using the GAM method.…”
Section: Climate-sensitive Site Index Modelmentioning
confidence: 99%
“…A variety of modeling approaches have been successfully applied to predict the site index from climate and other environmental variables. For instance, studies have used parametric modeling, such as multiple linear and nonlinear regressions (Chen et al 2002, McKenney & Pedlar 2003, Nigh et al 2004, Monserud et al 2006, Bravo-Oviedo et al 2007, Pinno et al 2009), as well as nonparametric modeling, such as classification and regression trees (Aertsen et al 2010, Afif-khouri et al 2011, generalized additive models (Albert & Schmidt 2009, Aertsen et al 2010, artificial neural networks and boosted regression trees (Aertsen et al 2010(Aertsen et al , 2011. After comparing the performance of five modeling techniques, Aertsen et al (2011) concluded that non-parametric models, such as Generalized Additive Models (GAM), were superior to traditional multiple linear regression in site index predictions.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geocentric approaches have been used as a basis for estimating SI or other measures of forest productivity and involve relating SI to various direct and/or indirect environmental factors [1]. Many studies have revealed environmental predictors of SI, using edaphic [2][3][4][5], topographic [6][7][8], and/or climatic [9][10][11] variables. Geocentrically-based (biophysical) SI models are independent from stand age and structure, usually have satisfactory prediction power and, therefore, provide tools that can effectively inform forest management.…”
Section: Introductionmentioning
confidence: 99%